Late onset heterozygous ornithine transcarbamylase deficiency mimicking complex partial status epilepticus. Issue 6 (1st December 2000) - Bogdanovic, M D; Kidd, D; Briddon, A; Duncan, J S; Land, J M
Abstract : A 57 year old woman with post-traumatic complex partial seizures was admitted because of recurrent episodes of altered mental state over the preceding 4 years, each lasting up to 5 days. There was a history of dietary protein intolerance since childhood and two of her daughters had died in the neonatal period from unexplained encephalopathies. In hospital she developed fluctuating confusion, amnesia, and sudden episodes of unresponsiveness. An EEG was consistent with complex partial status epilepticus but there was no response to benzodiazepines. Nasogastric feeding and sodium valproate were given and shortly afterwards she lapsed into a deep coma. Blood ammonia and urinary orotate were raised, and genetic testing confirmed that she was a carrier of a mutation in exon 3 of the ornithine transcarbamylase gene (C to T at position 92). Treatment with protein restriction, carnitine, and sodium phenylbutyrate led to a full recovery over a period of 3 months. To our knowledge this is the oldest age of onset yet described in a manifesting carrier. She is the fifth patient with heterozygous ornithine transcarbamylase deficiency reported to have had a severe reaction to sodium valproate. Hyperammonaemic encephalopathy should be considered in patients of any age who experience fluctuating confusion.